2013
DOI: 10.1016/j.jiph.2012.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus among Saudi National Guard Personnel: Seroprevalence and risk of exposure

Abstract: We report a 4% prevalence of HBsAg in the Saudi military population. This HBV prevalence was higher than those in the general Saudi population and military populations from Western countries. Both work-related and community-related risk factors for exposure are suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
0
6
1
Order By: Relevance
“…A large number of studies have been conducted in KSA,[15678910111213141516171819] and a systematic review pooling data of 312,787 people from 36 studies published between 1965 and 2013 found a prevalence of 3.2% for the country which is slightly lower than the worldwide prevalence of 3.6%. [1] In this systematic review, a decrease in prevalence has been observed over time, and hence it is expected that the current prevalence rate in KSA would be lower than the average found.…”
Section: Epidemiologymentioning
confidence: 99%
“…A large number of studies have been conducted in KSA,[15678910111213141516171819] and a systematic review pooling data of 312,787 people from 36 studies published between 1965 and 2013 found a prevalence of 3.2% for the country which is slightly lower than the worldwide prevalence of 3.6%. [1] In this systematic review, a decrease in prevalence has been observed over time, and hence it is expected that the current prevalence rate in KSA would be lower than the average found.…”
Section: Epidemiologymentioning
confidence: 99%
“…The same rate of HBV immunity was observed among air force personnel from South Brazil, 17 but this rate is lower than the rate reported among Saudi Arabia soldiers (57.5%), fire-fighters from Central Brazil (66.9%), Spanish military personnel (78.3%). 13,18,19 Nowadays the coverage of hepatitis B vaccination among children less than 18 months of age varies from 80 to 95%, 16 but the low prevalence of HBV immunity observed in the present study is probably due to the fact they were the first generation of compulsory vaccination.…”
Section: Discussionmentioning
confidence: 51%
“…A meta‐analysis of nine case‐control studies revealed a significant association between HBV infection and endoscopic examination (pooled OR, 2.21; 95% CI, 1.26‐3.86; p = 0.005), with a large amount of heterogeneity between trials (I 2 = 90%) (Fig. ) . When excluding the study by Jahangirnezhad and colleagues, heterogeneity (I 2 ) was reduced from 90 to 56%.…”
Section: Resultsmentioning
confidence: 98%
“…No articles documented the association between an endoscopic examination and HIV or T. pallidum . Details on the characteristics of the included studies are provided in Table …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation